ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) PADA SOAL UJIAN ASESMEN MADRASAH ALIYAH TAHUN 2024 - Delima, Desi Asmara; Hikmah, Hikmah; Masrun, Masrun (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the content of Higher Order Thinking Skills (HOTS) questions on the Ministry of Religious Affairs Madrasah Aliyah Assessment exam questions in 2024. This research uses a descriptive qualitative approach with content analysis method. The data analysis technique used is the Miles and Huberman model which includes four stages, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that the details of questions containing Higher Order Thinking Skills (HOTS) contained in the Ministry of Religious Affairs' Madrasah Aliyah Assessment exam questions in 2024 had a combination of various cognitive levels. The number of HOTS questions contained in the Ministry of Religious Affairs Madrasah Aliyah Assessment exam questions in 2024 from 40 items is 52.5%, and the number of LOTS questions contained in the Ministry of Religious Affairs Madrasah Aliyah Assessment exam questions in 2024 is 47.5%. Translated with DeepL.com (free version)